Navigation-Guided/Robot-Assisted Spinal Surgery: A Review Article - Lee, Young-Seok; Cho, Dae-Chul; Kim, Kyoung-Tae (Neurospine, 2024)
The development of minimally invasive spinal surgery utilizing navigation and robotics has significantly improved the feasibility, accuracy, and efficiency of this surgery. In particular, these methods provide improved accuracy of pedicle screw placement, reduced radiation exposure, and shortened learning curves for surgeons. However, research on the clinical outcomes and cost-effectiveness of navigation and robot-assisted spinal surgery is still in its infancy. Therefore, there is limited available evidence and this makes it difficult to draw definitive conclusions regarding the long-term benefits of these technologies. In this review article, we provide a summary of the current navigation and robotic spinal surgery systems. We concluded that despite the progress that has been made in recent years, and the clear advantages these methods can provide in terms of clinical outcomes and shortened learning curves, cost-effectiveness remains an issue. Therefore, future studies are required to consider training costs, variable initial expenses, maintenance and service fees, and operating costs of these advanced platforms so that they are feasible for implementation in standard clinical practice.